Preparation of transparent hydrophobic polymeric films spray-deposited on substrates - Viechineski, F. N.; Kubaski, E. T.; Schmidt, S. [UNESP]; Sequinel, T.; Varela, J. A. [UNESP]; Tebcherani, S. M. (SAGE Publications, 2018)
This paper describes the production of transparent hydrophobic polymeric films made of poly(vinyl chloride) and paraffin wax. A liquid polymeric solution was prepared and spray-deposited on silica glass and nonwoven fabric surfaces. The contact angle between water droplets and glass substrate was 102° while that between droplets and nonwoven fabric was 120°. The films exhibited hydrophobic behaviour regardless of the droplet size. Field emission gun scanning electron microscopy revealed complete adhesion of the film on the substrate and a film thickness of 0.16 µm. The atomic force microscopy micrographs showed a nanoscale rough film surface, which was responsible for air entrapment, preventing water from penetrating the film. This fact explains the high contact angle obtained. The raw materials also contributed to the film’s hydrophobicity because of their non-polarity, which prevents miscibility between water droplets and film.
Keywords: contact angle; glass substrate; Hydrophobicity; lotus effect; non-polar film; polymeric film; transparent film; water repellency